Maternal Depressive Symptoms Predict General Liability in Child Psychopathology. Issue 1 (2nd January 2022) - Swales, Danielle A.; Snyder, Hannah R.; Hankin, Benjamin L.; Sandman, Curt A.; Glynn, Laura M.; Davis, Elysia Poggi
ABSTRACT: Objective : The current study examines how maternal depressive symptoms relate to child psychopathology when structured via the latent bifactor model of psychopathology, a new organizational structure of psychopathological symptoms consisting of a general common psychopathology factor ( p -factor) and internalizing- and externalizing-specific risk. Method : Maternal report of depressive symptoms (Beck Depression Inventory – II) and child psychopathological symptoms (Child Behavior Checklist and Children's Behavior Questionnaire) were provided by 554 mother-child pairs. Children in the sample were 7.7 years old on average ( SD = 1.35, range = 5–11 years), and were 49.8% female, 46% Latinx, and 67% White, 6% Black, 5% Asian/Pacific Islander, and 21% multiracial. Results : Maternal depressive symptoms were positively associated with the child p -factor but not with the internalizing- or externalizing-specific factors. We did not find evidence of sex/gender or race/ethnicity moderation when using latent factors of psychopathology. Consistent with past research, maternal depressive symptoms were positively associated with internalizing and externalizing composite scores on the Child Behavior Checklist. Conclusions : Findings suggest that maternal depressive symptoms are associated with transdiagnostic risk for broad child psychopathology ( p -factor). Whereas the traditional Achenbach-style approach of psychopathological assessment suggests that maternal depressive symptoms are associated with both child internalizing and externalizing problems, the latent bifactor model suggests that these associations may be accounted for by risk pathways related to the p -factor rather than internalizing or externalizing specific risk. We discuss clinical and research implications of using a latent bifactor structure of psychopathology to understand how maternal depression may impact children's mental health.